Water Reductive Effect of Lymphaticovenular Anastomosis on Upper-Limb Lymphedema: Bioelectrical Impedance Analysis and Comparison with Lower-Limb Lymphedema - Yasunaga, Yoshichika; Yanagisawa, Daisuke; Nakajima, Yuta; Mimura, Shinei; Kobayashi, Miharu; Yuzuriha, Shunsuke; Kondoh, Shoji (Journal of Reconstructive Microsurgery, 2020)
Background We previously examined the water reductive effect of lymphaticovenular anastomosis (LVA) using bioelectrical impedance analysis (BIA) measurement on lower-limb lymphedema and revealed mean water volume reduction and edema reduction rate by leg LVA to be 0.86 L and 45.1%, respectively. This study aimed to clarify the water reductive effect of LVA on arm lymphedema and compare its results with those for leg lymphedema.Patients and Methods The efficacy of LVA for unilateral arm lymphedema was evaluated using BIA in a retrospective cohort. Limb circumference and arm body water volume (ABW) of the affected and unaffected arms were measured before and after LVA. Mean water volume reduction (ΔABW) and edema reduction rate by arm LVA were compared with values for leg LVA cited from our previous report as a historical control.Results Nineteen consecutive patients were enrolled. The mean ΔABW and edema reduction rate by BIA were 0.267 L and 46.0%, respectively. The decreasing rate of ABW by BIA was significantly larger than those of the upper extremity lymphedema index and sum of 5 circumferences measurement methods. ΔABW could be predicted by a regression line based on the preoperative water volume difference between affected and unaffected limbs. The mean edema reduction rates for arm and leg LVA were comparable.Conclusion The water reductive effect of LVA on upper-limb lymphedema was demonstrated by BIA assessment. BIA can reflect the effect of LVA more sensitively than conventional objective measurements and may facilitate the interpretation of LVA results. Although water volume reduction by arm LVA was less than that by leg LVA, the edema reduction rates were comparable.
Keywords: lymphedema; lymphaticovenular anastomosis; bioelectrical impedance analysis